Direct and indirect drivers of grassland bird population declines and settlement decisions over broad spatial and temporal scales - Smith, Dylan J. (Kansas State University, 2021)
Many North American bird populations are declining, and of those, grassland bird populations are declining most rapidly, having been reduced by about half since 1970. Such declines are difficult to study, both because grasslands are characterized and maintained by disturbance, and because grassland birds have a high propensity for dispersal. The primary cause for population declines is habitat loss. For example, only ~14% of pre-European colonization eastern tallgrass prairie remains intact. Even where habitat remains, many species continue to decline, and these declines may be due to reductions in reproductive success. One potential cause of these local declines is the encroachment of woody vegetation on grasslands, which for grassland birds reduces the overall amount and degrades the quality of usable habitat. In addition, local demographic changes cause—and are caused by—regional- or continental-scale patterns. Thus, broad spatial approaches are needed to best understand the drivers of demographic change. In my first chapter, I sought to identify whether woody encroachment, via reductions in reproductive success, can explain changes in population abundance. I compiled and analyzed data on nest contents and nest success collected at Konza Prairie Biological station over nearly five decades. Nest success did not change since 1971, but the frequency of Brown-headed Cowbird (Molothrus ater) brood parasitism increased. In addition, grassland obligates were harder hit than species that prefer woodier habitat, supporting the idea that grassland degradation most strongly affects birds that rely on pristine prairie. In chapter 2, I tested alternative mechanisms linking the high degree of climatic variability in the Great Plains to inter-annual fluctuations breeding distribution and local abundance of a common grassland bird species, Grasshopper Sparrows (Ammodramus savannarum perpallidus). I used 11 years of citizen science data from eBird spanning the entire Great Plains to determine whether overwinter mortality, temperature during migration, or precipitation during the preceding year’s growing season and vegetation phenology best predicted local abundance. The start date of the growing season and the total precipitation in the preceding year’s growing season correlated most strongly with sparrows’ interannual settlement decisions. Local abundance was highest in areas where the growing season started before March and where the preceding year’s growing season precipitation was low. The drivers of population declines and movement decisions in grassland birds are complex and often indirect or delayed. As grasslands face ongoing anthropogenic threats ranging from agricultural development to fire suppression and climate change, identifying the distributional and demographic responses of grassland birds will be crucial to conserving this declining group of species.
Keywords: Grassland birds; Avian reproduction; Weather; Movement decisions; Great Plains; Conservation